2012
DOI: 10.1039/c2cc35291e
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated ionic liquids (ENILs): from continuous to discrete liquid phase

Abstract: Encapsulated ionic liquid (ENIL) material was developed, consisting of ionic liquid (IL) introduced into carbon submicrocapsules. ENILs contain >85% w/w of IL but discretized in submicroscopic encapsulated drops, drastically increasing the surface contact area with respect to the neat fluid. ENIL materials were here tested for gas separation processes, obtaining a drastic increase in mass transfer rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 27 publications
11
87
0
Order By: Relevance
“…However, one of the main drawback for the application of SILP materials in gas separation processes is the limited amount of IL uploaded onto the support (generally lower than 20% w/w [45], reaching up to 50% w/w in some cases [40,46]), that limits their application in gas separation processes. In this context, the new concept of encapsulated ionic liquids (ENILs) has arisen as an interesting alternative [47][48][49][50][51][52][53]. In a pioneer work, Deng et al synthesized a highly dispersed IL material through the physical encapsulation of the IL in a silica-gel matrix through a sol-gel process, thus reaching IL contents from 8 to 53 % w/w [47].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one of the main drawback for the application of SILP materials in gas separation processes is the limited amount of IL uploaded onto the support (generally lower than 20% w/w [45], reaching up to 50% w/w in some cases [40,46]), that limits their application in gas separation processes. In this context, the new concept of encapsulated ionic liquids (ENILs) has arisen as an interesting alternative [47][48][49][50][51][52][53]. In a pioneer work, Deng et al synthesized a highly dispersed IL material through the physical encapsulation of the IL in a silica-gel matrix through a sol-gel process, thus reaching IL contents from 8 to 53 % w/w [47].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites of ILs confined in mesoporous silica gels were successfully applied to the selective adsorption of CO 2 /N 2 streams [48]. We recently presented ENIL materials [53] consisting of hollow carbonaceous submicrocapsules (C cap ) that confine ILs [54][55][56]. The synthesis of ENILs is favored by the high affinity found between ILs and AC [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables the immobilization of ionic liquids, without changing their molecular structure. Recently, a number of groups demonstrated encapsulation of ionic liquids [42][43][44][45][46][47][48][49][50][51][52][53][54][55]; in 2012 Palmor et al demonstrated encapsulation of ionic liquid within a carbon shell via direct impregnation [47]. A year later Minami and co-workers encapsulated 1-hexyl-3-methyl imidazolium bis(trifluoromethane sulfonyl)amide ([Hmim][TFSA]) by microsuspension polymerization [45].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), generally defined as organic salts that melt below 100 ∘ C, have been closely studied because they are designable, thermally stable, nonvolatile, and capable of dissolving even polymeric compounds [5][6][7]. Such properties have led to an explosion in their applications as green, designable solvents for a variety of processes linked to green chemistry and clean technology [8][9][10]. The introduction of the specific functional group in ionic liquid anions or cations is to form functional ILs [11,12].…”
Section: Introductionmentioning
confidence: 99%